Army Integrated Combat Model for Synthetic Force based on Information Cognition. (April 2020) - Du, Jian; Xia, Jing; Li, Huizhen
Abstract: Army integrated warfare presents a nonlinear form of system confrontation, which not only changes the decisive factors of combat victory, but also makes the complex interrelations in the system more chaotic. Based on the theory of complex adaptive system, land battle is regarded as a complex system with hierarchical inrush, nonlinear, self-organizing, decentralized control. The integrated combat model of army is established, the influence of firepower, maneuverability, communication perception and other factors on the overall combat capability of the army is studied, the factors are optimized, and the optimal scheme of combat force operation is put forward. It provides certain theoretical support for the development of military weapons and equipment, the rational allocation of troops and the organization of combat coordination in the future.